2014
DOI: 10.1002/ijfe.1504
|View full text |Cite
|
Sign up to set email alerts
|

The Exchange Rate Disconnect Puzzle Revisited

Abstract: A long-standing puzzle in the international macroeconomic literature has been the weak link between the theoretical foundations of the monetary approach to exchange rate determination and its empirical validity. This paper aims at filling this gap. We use a different econometric methodology; the Autoregressive Distributed Lag approach to cointegration, to show that exchange rates and fundamentals move together in the long-run, thus providing support to the monetary model. We also show that fundamentals Granger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
(82 reference statements)
0
4
0
1
Order By: Relevance
“…Katusiime, et al (2015) analyses the relation between Uganda Shilling/US$ and monetary fundamentals and finds that hybrid model provides support to analyse the Uganda Shilling/US$ exchange rates behaviors. Similarly, Bahmani-Oskooee, et al (2015) investigated the link between exchange rate and monetary factors for six countries, using the Autoregressive Distributed Lag (ARDL). This study found supportive evidence for the validity of monetary exchange rate model.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Katusiime, et al (2015) analyses the relation between Uganda Shilling/US$ and monetary fundamentals and finds that hybrid model provides support to analyse the Uganda Shilling/US$ exchange rates behaviors. Similarly, Bahmani-Oskooee, et al (2015) investigated the link between exchange rate and monetary factors for six countries, using the Autoregressive Distributed Lag (ARDL). This study found supportive evidence for the validity of monetary exchange rate model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ARDL model is considered to be superior over Johansen's (1995) cointegration test. The Johansen's test selected same lag order for all the variables, while ARDL can take different lags for different variables [Bahmani-Oskooee, et al (2015)]. This approach is directly applicable, irrespective of whether the variables are I(0), I(1) or mutually integrated.…”
mentioning
confidence: 99%
“…7 This measure offers consistent units -with a percentage change of the exchange rate that is suitable for cross-country comparisons and analysis across time. Secondly, we use an estimation approach, namely the autoregressive distributed lag modeling (ARDL) technique suggested by Pesaran et al (2001), which is appropriate for mixed order integration variables avoiding the information loss by taking the first difference of non-stationary series (Bahmani-Oskooee, Hosny, and Kishor, 2015). Earlier studies have either ignored the unit root issue or took the first difference Akram and Byrne, 2015;Patnaik and Pundit, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This could be the key issue explaining why many studies could not find a direct link between the fundamentals and exchange rates. Bahmani-Oskooee, Hosny, and Kishor (2015) showed that fundamentals Granger-cause exchange rates, both in the short run and long run. However, the relationship between the exchange rate and its fundamentals in the short run was not found to be very clear, especially in the era of high exchange rate volatility, where the spot exchange rate may be influenced by a number of other possibly unobserved variables.…”
mentioning
confidence: 99%